Comet/Asteroid Impacts and Human Society An Interdisciplinary Approach - Bobrowsky, Peter T.; Rickman, Hans.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
In 1908 an atmospheric explosion in northern Siberia released energy equivalent to 15 Mton of TNT. Can a comparable or larger NEO affect us again? When the next NEO strikes Earth will it be large enough to destroy a city? Will the climate change significantly? Can archaeology and anthropology provide insights into the expected cultural responses with NEO interactions? Does society have a true grasp of the actual risks involved? Is the Great Depression a good model for the economic collapse that could follow a NEO catastrophe? This volume provides a necessary link between various disciplines and comet/asteroid impacts.
Anthropology, Archaeology, Geology -- The Geologic Record of Destructive Impact Events on Earth -- The Archaeology and Anthropology of Quaternary Period Cosmic Impact -- The Sky on the Ground: Celestial Objects and Events in Archaeology and Popular Culture -- Umm al Binni Structure, Southern Iraq, as a Postulated Late Holocene Meteorite Impact Crater -- Tree-Rings Indicate Global Environmental Downturns that could have been Caused by Comet Debris -- The GGE Threat: Facing and Coping with Global Geophysical Events -- Astronomy and Physical Implications -- The Asteroid Impact Hazard and Interdisciplinary Issues -- The Impact Hazard: Advanced NEO Surveys and Societal Responses -- Understanding the Near-Earth Object Population: the 2004 Perspective -- Physical Properties of NEOs and Risks of an Impact: Current Knowledge and Future Challenges -- Evaluating the Risk of Impacts and the Efficiency of Risk Reduction -- Physical Effects of Comet and Asteroid Impacts: Beyond the Crater Rim -- Frequent Ozone Depletion Resulting from Impacts of Asteroids and Comets -- Tsunami as a Destructive Aftermath of Oceanic Impacts -- The Physical and Social Effects of the Kaali Meteorite Impact — a Review -- The Climatic Effects of Asteroid and Comet Impacts: Consequences for an Increasingly Interconnected Society -- Nature of the Tunguska Impactor Based on Peat Material from the Explosion Area -- The Tunguska Event -- Tunguska (1908) and Its Relevance for Comet/Asteroid Impact Statistics -- Atmospheric Megacryometeor Events versus Small Meteorite Impacts: Scientific and Human Perspective of a Potential Natural Hazard -- Socio-Economic and Policy Implications -- Social Science and Near-Earth Objects: an Inventory of Issues -- Perception of Risk from Asteroid Impact -- Hazard Risk Assessment of a Near Earth Object -- Social Perspectives on Comet/Asteroid Impact (CAI) Hazards: Technocratic Authority and the Geography of Social Vulnerability -- May Land Impacts Induce a Catastrophic Collapse of Civil Societies? -- The Societal Implications of a Comet/Asteroid Impact on Earth: a Perspective from International Development Studies -- Disaster Planning for Cosmic Impacts: Progress and Weaknesses -- Insurance Coverage of Meteorite, Asteroid and Comet Impacts — Issues and Options -- The Economic Consequences of Disasters due to Asteroid and Comet Impacts, Small and Large -- Communicating Impact Risk to the Public -- Impact Risk Communication Management (1998–2004): Has It Improved? -- Towards Rational International Policies on the NEO Hazard -- A Road Map for Creating a NEO Research Program in Developing Countries.
Keywords: Astronomy; Astrophysics; Geology; Human geography; Environmental economics; Archaeology; Astronomy, Astrophysics and Cosmology; Geology; Human Geography; Environmental Economics; Archaeology